Forum profesorskieNeurocutaneous disorders – advances in diagnosis and management - Domańska-Pakieła, Dorota; Kaczorowska, Magdalena; Borkowska, Julita; Kotulska, Katarzyna; Jóźwiak, Sergiusz (Dermatology Review/Przegląd Dermatologiczny, 2009)
This article presents the most frequent neurocutaneous disorders, their age-dependent clinical features, diagnostic and follow-up procedures, and management.